SISTEM EKOLOGI MASYARAKAT MINANGKABAU DALAM LAGU SOSOH PADA RITUAL TABUIK DI PARIAMAN SUMATRA BARAT - CAMERON MALIK (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2016)
Sosoh song is a song that is played when the ritual took place tabuik. The existence of this song in the context of the ritual aims to facilitate the battle for ritual. Because the ritual aims to represent back tabuik experienced war Husein in Padang Karbala, Iraq. But the song is not only associated with ritual context but also the overall context of the Minangkabau culture. This indicates there is a reciprocal relationship between the songs with the construction of culture. In the view of ecology song of sosoh seen in the context of its relationship with the environment: both natural and social. Ecological thinking more emphasis on the aspect of relationships, networks and sustainability in a living system. Therefore sosoh tracks seen from the relationship and network with Minangkabau culture system as a whole.